Quantification of material flows: A first step towards integrating tomato greenhouse horticulture into a circular economy. (15th December 2022) - van Tuyll, Alexander; Boedijn, Alexander; Brunsting, Martine; Barbagli, Tommaso; Blok, Chris; Stanghellini, Cecilia
Abstract: Reducing environmental impact is a necessary condition for sustainability, but it is not a sufficient one. The current 'linear' economy not only leads to environmental impact; it also depletes finite natural reserves. This is why moving towards a more 'circular' economy is desired. One of the obstacles in implementing a circular economy are knowledge gaps about the nature and quantity of input and output flows of production processes. The aim of this paper is not to quantify environmental impact, but rather to bridge these knowledge gaps for a particular type of vegetable production, by detailing the resource input and output of a typical high-tech glasshouse tomato crop in the Netherlands. In particular, this paper has focused on material flows potentially suitable for relatively short-term re-use and/or substitution in a circular economy. The paper describes how figures have been collected about the sub-processes involving each of the material flows, the accuracy and range of such numbers, and how their consistency can be finally verified. After combining all numbers into three diagrams, this paper finally discusses the potential and obstacles for recycling of each of the material flows discussed. For instance, the results show that there is a good potential for recovering minerals from non-fruit biomass, where over half of Mg, Ca and S end up, at 58%, 70% and 70% respectively. However, its being virtually inextricably mixed with plastic is a huge barrier, requiring changes such as biodegradable plastics. Finally, by quantifying the flows per unit of produce (1 kg tomato), this paper provides numbers for dimensioning possible symbiotic production processes, such as aquaculture or animal husbandry. Graphical abstract: Image 1 Highlights: We quantify six flows of consumables per kg tomato yield in a Dutch greenhouse. At least half of the water, CO2, and nutrients supplied does not end up in the tomato. No matter how efficient, greenhouse horticulture needs to become more circular. Results from various sources lead to a consistent order of magnitude. Most Ca, Mg and S goes to non-yield biomass, showing potential for recovery.